ADHESIVE CAPSULITIS; MANAGEMENT BY PHYSIOTHERAPY VERSUS INTRA-ARTICULAR CORTICOSTEROID INJECTION: Adhesive Capsulitis Management - Hashmi, Muhammad Umair; Chughtai, Babar Bakht; Ahsan, Muhammad Nadeem (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine outcomes of intra-articular corticosteroids injection versus physiotherapy for the treatment of adhesive capsulitis using mean pain score on the visual analogue scale.Study Design: Comparative prospective study. Place and Duration of Study: Orthopedic outpatient department, Bahawal Victoria Hospital Bahawalpur from Jan to Jun 2021.Methodology: A total of 120 cases having adhesive capsulitis (frozen shoulder) were included in the study according to inclusion criteria. Non-probability consecutive sampling technique was used for the selection of cases. Patients were divided into two groups, group-A and group B, each containing 60 cases. Patients in group-A were given intra-articular steroid injection (2ml triamcinolone 40mg ± 2ml of bupivacaine). Patients in group B received ten sessions of physiotherapy by a welltrained physiotherapist under the supervision of an orthopaedic surgeon on alternate days. After six weeks, outcomes were measured in terms of pain score using a visual analogue pain scale.Results: Significant improvement was seen among patients in group-A with mean pain score from 7.32 ± 0.89 measured initially to 5.44 ± 1.37 measured after six weeks (p0.05).Conclusion: Significant improvement in pain relief can be achieved using intra-articular steroid injection administered in the shoulder as compared to supervised sessions of physiotherapy among patients with adhesive capsulitis.